2008
DOI: 10.1111/j.1365-2044.2008.05627.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on pulmonary inflammatory response and dysfunction induced by cardiopulmonary bypass*

Abstract: SummaryThe pulmonary inflammatory response and pulmonary dysfunction after cardiopulmonary bypass is a major problem in patients undergoing cardiac surgery. Propofol has anti-inflammatory and immunomodulatory properties which may attenuate this response. Thirty patients undergoing cardiopulmonary bypass were randomly assigned to receive saline (control group) or propofol (propofol group). Pulmonary thoracic compliance, respiratory index, malondialdehyde and interleukin-8 concentrations and intrapulmonary polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Studies have reported that the cardioprotection mechanism of inhaled anesthetics such as, volatile anesthetics open intracellular K ATP channels, activate adenosine receptors, and inhibit Na + /K + pump [1, 8, 28, 29]. Studies have also reported that the cardioprotection mechanism of propofol is related to its anti-inflammatory, immunomodulatory and antioxidant properties [21, 30, 31]. Nevertheless, many studies, such as some prospective randomized controlled trials [1013, 32] and observational study [14] in adult patients indicated some contradicting results on the cardioprotection between volatile and non volatile agents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the cardioprotection mechanism of inhaled anesthetics such as, volatile anesthetics open intracellular K ATP channels, activate adenosine receptors, and inhibit Na + /K + pump [1, 8, 28, 29]. Studies have also reported that the cardioprotection mechanism of propofol is related to its anti-inflammatory, immunomodulatory and antioxidant properties [21, 30, 31]. Nevertheless, many studies, such as some prospective randomized controlled trials [1013, 32] and observational study [14] in adult patients indicated some contradicting results on the cardioprotection between volatile and non volatile agents.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In lean animals, PRO decreases airway resistance and lung inflammation in experimental acute lung injury induced by endotoxin, 6,7 ischemia-reperfusion, 8 or oleic acid. 9 Similarly, in lean human subjects, PRO improves lung mechanics, 10 reduces inflammation, 11 and modulates oxidative stress. 12 Likewise, DEX has shown beneficial effects on lung mechanics, 13 inflammation, 14,15 and oxidative stress 16 in lean animals and humans.…”
mentioning
confidence: 99%
“…In animal studies, propofol has decreased cytokine release during sepsis (2,3) and reduced neutrophil-mediated inflammation in acute pulmonary injury (4,5). In human studies, propofol has attenuated myocardial reperfusion injury and pulmonary dysfunction following cardiopulmonary bypass by reducing free radical release and modulating the inflammatory process (6,7).…”
mentioning
confidence: 99%
“…Similarly, in lung injury models, inappropriately activated neutrophils have resulted in acute respiratory distress syndrome or transfusion-related acute lung injury (19,20). Interestingly, it has been shown in animal and human studies that propofol may diminish the oxidative or inflammatory injury induced by neutrophils (2,4,7). These observations are interpreted to mean that propofol has an antioxidant capacity.…”
mentioning
confidence: 99%